Evaluation of a Case Management to Support Families With Children Diagnosed With Spinal Muscular Atrophy—Protocol of a Controlled Mixed-Methods Study - Willems, Jana; Farin-Glattacker, Erik; Langer, Thorsten (Frontiers in Pediatrics, 2021)
Background: Spinal muscular atrophy (SMA) is a rare neuromuscular disease characterized by degeneration of the anterior horn cells in the spinal cord, resulting in muscle atrophy and proximal muscle weakness. SMA presents with a wide range of symptoms requiring multiple clinical specialists and therapists. Integrating care between disciplines can be challenging due to the dynamic course of the disease, and great distances between specialist centers and local providers. Insufficient care integration can lead to suboptimal quality of care and more difficulties for patients and families. This study aims to improve care integration through a Case Management intervention, and taking a mixed-methods approach, to evaluate its impact. Methods: An exploratory, controlled, two-armed study with baseline, post- and follow-up measurement and process evaluation is conducted to evaluate our intervention compared to usual care. Through a multi-perspective state analysis, we investigate the experiences of caregivers and healthcare providers concerning the actual healthcare quality of patients with SMA I and II. Semi-structured interviews and care diaries are used. We apply that data to conceive a tailored Case Management intervention supplemented by a digital platform. The intervention’s effect is examined in comparison to a control group taking a mixed-methods approach. As primary endpoints, we investigate the caregivers’ health-related quality of life and the quality of care integration. Secondary endpoints are the use of healthcare services (patients and caregivers) and costs. We assess the process quality from the perspectives of caregivers and healthcare providers through semi-structured interviews. Discussion: This is an exploratory, controlled study to assess the impact of a tailored Case Management intervention to improve the care of patients with SMA I and II. After the evaluation, results on feasibility, expected effect sizes, and process quality will be available. On this basis, future randomized controlled trials can be planned. If demonstrated beneficial, the experience gained within this study may also be valuable for care strategies in other regions and other (non-pediatric) patient groups with rare diseases and/or chronic, complex conditions. Trial registration: German Clinical Trials Register (DRKS): DRKS00018778; Trial registration date 05. December 2019 - Retrospectively registered; https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00018778.